$\large \begin{cases} a_1 =5 \\ a_{n+1}=\dfrac{1+\sqrt3 a_n}{\sqrt3 -a_n} & \text{for } n \ge 2 \end{cases}$

A sequence $\{a_n\}$ satisfies the recurrence relation above. Find $a_{100}$ .

5
$-\frac{13\sqrt3}{11}-\frac{10}{11}$
$-\frac{1}{5}$
$-\frac{13\sqrt3}{37}-\frac{10}{37}$

**
This section requires Javascript.
**

You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.

Let $a_n = \tan \theta_n$ , then we have, for $n \ge 2$ ,

$\begin{aligned} a_{n+1} & = \frac {1+\sqrt 3 a_n}{\sqrt 3 - a_n} \\ \tan \theta_{n+1} & = \frac {1+\sqrt 3 \tan \theta_n}{\sqrt 3 - \tan \theta_n} = \frac 1{\tan \left(\frac \pi 3 - \theta_n\right)} = \cot \left(\frac \pi 3 - \theta_n\right) = \tan \left(\frac \pi 2 - \frac \pi 3 + \theta_n \right) = \tan \left(\frac \pi 6 + \theta_n \right) \end{aligned}$

$\begin{aligned} \implies \theta_{n+1} & = \frac \pi 6 + \theta_n \\ \theta_n & = \frac {(n-1)\pi} 6 + \color{#3D99F6}\theta_1 & \small \color{#3D99F6} \text{where }\theta_1 = \tan^{-1} 5 \\ \implies a_{100} & = \tan \theta_{100} \\ & = \tan \left(\frac {(100-1)\pi} 6 + \tan^{-1} 5\right) \\ & = \tan \left(16\frac 12 \pi + \tan^{-1} 5\right) \\ & = \tan \left(\frac \pi 2 + \tan^{-1} 5\right) & \small \color{#3D99F6} \text{Note that }\tan (\pi -x) = - \tan x \\ & = - \tan \left(\frac \pi 2 - \tan^{-1} 5\right) \\ & = - \cot \left(\tan^{-1} 5\right) \\ & = \boxed{- \dfrac 15} \end{aligned}$